Perceptual development of Mexican school children as measured by responses to The Holtzman Inkblock Technique - Swartz, Jon D.; Lara Tapia, Luis; Thorpe, Joseph S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
In order to test the generality of earlier findings regarding the relationship between level of perceptual development and scores on variables from the Holtzman Inkblot Technique (H IT), a comparable sample of children in another culture— 300 normal Mexican school children from Mexico City, comprising three criterion age groups, 6.7, 9.7, and 12.7 years of age—were tested in a replication of an earlier investigation in the United States. Each group contained 50 males and 50 females. Two-way classification (sex-by-age) analyses of variance of 1 1 selected HIT variables revealed only two significant sex differences and no significant sex-by-age interactions. Age-group differences beyond the .001 level of significance, however, were found for eight of the 1 1 variables studied, with seven showing consistent monotonic increases with age. Five of these seven variables—Form Appropriateness, Form Definiteness, Movement, Integration, and Human—are those which proved to be reliable and meaningful indices of perceptual development in previous studies with the HIT in the United States. These results are interpreted as providing strong support for the several HIT scores as indices of perceptual development and as confirming the nature and direction of this development, despite marked geographical and cultural differences in the subject population sampled.